HUBUNGAN FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL DENGAN TINGKAT PARTISIPASI ANGGOTA KELOMPOK PETANI PEMAKAI AIR (KP2A) (STUDI KASUS DI KECAMATAN SEGINIM KABUPATEN BENGKULU SELATAN) - Purwoko, Agus; Yuliarso, M. Zulkarnain; Ardiyansyah, . (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
This research aim to know internal factors and eksternal relation with participation rate the members of water users farmers group in Subdistrict of Seginim of Regency of Bengkulu South arch. This research conducted on 1-15 August 2006 in Subdistrict of Seginim of Regency of Bengkulu South arch. Responder determination conducted with Samle Random Sampling, where responder amount taken by as much 60 responder. Model Rank-Spearmans used to conduct expense function analysis, while for the input levying conducted by a analysis descriptively.Result of research indicate that egoism rate, perception, motivation and communication have a significant relation with participation rate the members of water user farmers group in Subdistrict of Seginim of Regency of Bengkulu South arch.